The effect of nitric oxide supplementation therapies in the hemodynamic response and outcome during hemorrhagic shock in an animal model (2016)
Nitric oxide (NO) production is impaired after hemorrhagic shock (HS) due to reduced vascular endothelial shear stress (SS); uncoupling of endothelial NO synthase (eNOS) and hypoxia. We propose to supplement NO during resuscitation, using NO releasing nanoparticles (NO-np) and inhaled NO. Preliminary hemorrhagic shock and resuscitation studies, using Golden Syrian hamsters showed that NO therapies (NO-np at 5 mg/kg, 10 mg/kg, 15 mg/kg, 20 mg/kg and 40 mg/kg and inhaled NO at 89 ppm and 189 ppm) improved systemic and microcirculatory hemodynamic parameters, being the 15 mg/kg NO-np therapy superior. Subsequent 8-day survival tests where developed showing superior decisive results when compared to conventional fluid resuscitation therapies. Afterwards, an animal scale up swine model was instrumented with a Swan Ganz catheter to monitor systemic hemodynamics as mean arterial pressure (MAP), heart rate (HR), cardiac output (CO), and pulmonary artery pressures and blood chemistry. HS was induced in the swine model by withdrawing 50% of the animal's blood volume (BV) in 10 mins, HS was maintained for 60 mins, and then animals were resuscitated with 50% of the shed volume of Voluven@ (HES) containing 15 mg/kg of NO-np